THE RESEARCH IN VOCATIONAL TRAINING IN PHYSICAL EDUCATION: SOME POSSIBILITIES (Fiep Bulletin - online, 2011)
Analyzes the formative possibilities for research use and its contribution to the professional training of physical education. This is a literature which studies production-related research topic in the process of training. It is understood the research as a tool for training and work, which can be a professional investigative practice. As syntheses of considerations, it appears that work is necessary for the formation favors the research process throughout the historical trajectory of academic and non-timely manner, in order to increase the possibilities of forming investigative professionals.
Keywords: research; training; physical education